Restructuring And Clamour For True Federalism In Nigeria: A Comparative Analysis - Adedeji, Adebayo O.; Ezeabasili, Ifeoma E. (Advances in Social Sciences Research Journal, 2018)
Federalism has been given several meaning such that the new lexicons on the subject in Nigeria are ‘true’ and restructuring. However, the concept has more of a normative dimension than an empirical interpretation. This makes it difficult to generalize across the various political systems that haveadopted a federal system. The primary aim of federalism is to accommodate diversity in a single entity. The challenge however lies in the underlining principle of federalism that will be suitable in resolving salient political issues in these societies. The debate often has resolve around the ideal model of federal arrangement that is suitable across time and space. While there have been diverse perspectives of federalism and its operations, consensus on the ideal model is still lacking. Thus, bringing to the fore arguments that federalism is a means to an end and not an end in itself. Consequently, the issues that necessitate the adoption of federalism should be the emphasis of the principles of federalism and not the adoption of a model that may not adequately capture the peculiarities of those societies. This paper attempts a conceptualisation of the concept and makes a comparison of its practice in United States of America and Nigeria.